Evaluation of In-Vitro Antioxidant Potential and Antimicrobial Activity of Nephrolepis biserrata (sw.) Schott. Leaf Extracts - Singh, Sonia (Anti-Infective Agents, 2022)
Objective: This study aims to determine the in vitro antioxidant and antimicrobial properties of Nephrolepis biserrata (Sw.) Schott leaf extracts against different microbial strains, including 4 gram-positive bacteria, 4 gram-negative bacteria, 3 yeast, and 4 mould. Methods: The agar well diffusion method examined the antimicrobial activity of Nephrolepis biserrata leaf extracts against test micro-organisms. Additionally, TPC (total phenolic content), TFC (total flavonoid content), and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) free radical assay of extracts were determined. Results: Preliminary phytochemical screening of all three extracts revealed the presence of tannins, terpenoids, alkaloids, saponin glycosides, and flavonoids. Results obtained were compared with the antibiotics Amphotericin B, Fluconazole, and Gentamicin used as standards. The mean zones of inhibition of methanol extract varied from 7 to 25 mm. However, with petroleum ether extract, the range varied from 9 to 12 mm and with acetone extract, the range was from 8 to 13 mm at two different concentrations of 250 and 500μg/disc. All extracts possessed significant antimicrobial activity against bacterial strains including Bacillus cereus, B. subtilis, Staphylococcus aureus, S. epidermis, Pseudomonas aeuginosa, Escherichia coli, Proteus Vulgaris, and Klebsiella pneumonia compared to fungal microbes such as Cryptococcus luteolus, Candida albicans, C. tropicalis, Aspergillus candidus, A. niger, and Mucor hiemalis wehmer, respectively. However, amongst all the three extracts, methanol leaf extract showed maximum antimicrobial activity. Conclusion: From the present study, it has been summarized that the antimicrobial activity of plants might be due to the presence of flavonoids and tannin components. In conclusion, still advanced research is required to isolate the active principles from plant extracts, showing antimicrobial activity that may lead to the development of a phytomedicine.
Keywords: methanol